Bilateral Linear Lichen Planus Pigmentosus Associated with Hepatitis C Virus Infection - Vasanop Vachiramon (Case Reports in Dermatology, 2010)
Lichen planus pigmentosus is a rare subtype of lichen planus. We report a first case of lichen planus pigmentosus with bilateral linear distribution associated with hepatitis C virus infection. The lesion was improved after sun avoidance and treatment of hepatitis C virus infection with a combination of interferon and ribavirin. This case stresses the importance of screening for hepatitis C virus infection as lichen planus pigmentosus can be an associated condition.